Brill's Companion to Callimachus - Acosta-Hughes, Benjamin. (Brill's Companions to Classical Studies., 2011)
Few figures from Greco-Roman antiquity have undergone as much reassessment in recent decades as Callimachus of Cyrene, who was active at the Alexandrian court of the Ptolemies during the early third century BC. Once perceived as a supreme example of ivory tower detachment and abstruse learning, Callimachus has now come to be understood as an artificer of the images of a powerful and vibrant court and as a poet second only to Homer in his later reception. For the modern audience, the fragmentation of his texts and the diffusion of source materials has often impeded understanding his poetic achievement. Brill's Companion to Callimachus has been designed to aid in negotiating this scholarly terrain, especially the process of editing and collecting his fragments, to illuminate his intellectual and social contexts, and to indicate the current directions that his scholarship is taking.